2015
DOI: 10.1186/s40662-015-0021-7
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond laser cataract surgery

Abstract: Femtosecond laser (FSL) cataract surgery is in its infancy but is rapidly gaining popularity due to the improved consistency and predictability for corneal incisions and anterior capsulorhexis. It enables subsequently less phacoemulsification energy and time to be employed, which has gains in terms of reduced corneal oedema. In addition, the FSL allows better circularity of the anterior capsulotomy, capsule overlap, intraocular lens (IOL) placement and centration of the IOL. These advantages have resulted in i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 73 publications
2
49
0
Order By: Relevance
“…Although the results did not reach statistical significance, Seidel testing showed that the mean IOP at which leakage occurred was higher for the FS laser, indicating sealability to be better with the FS laser-generated CCI. As discussed in the recent review by Nagy and McAlinden, 24 FS lasers deliver consistent and precise multiplanar incisions, which are an integral part of securely controlling the avenue where infectious materials are less likely to navigate. At low IOP levels, wounds created by manual corneal incisions could become unstable, potentially risking entry of bacteria.…”
Section: Discussionmentioning
confidence: 98%
“…Although the results did not reach statistical significance, Seidel testing showed that the mean IOP at which leakage occurred was higher for the FS laser, indicating sealability to be better with the FS laser-generated CCI. As discussed in the recent review by Nagy and McAlinden, 24 FS lasers deliver consistent and precise multiplanar incisions, which are an integral part of securely controlling the avenue where infectious materials are less likely to navigate. At low IOP levels, wounds created by manual corneal incisions could become unstable, potentially risking entry of bacteria.…”
Section: Discussionmentioning
confidence: 98%
“…Recently a femtosecond laser (FSL) has been introduced into phacoemulsification cataract surgery to open the lens capsule, fragment the cataract, and make corneal incisions, with corneal scarring being the only absolute contraindication for its use. 27 FSL-assisted cataract surgery, compared to the conventional technique, requires less phacoemulsification energy and time, which may reduce the thermal injury to ocular tissues by ultrasound and corneal edema. 27 , 28 Greater precision in stages of cataract surgery performed with FSL is suggested to improve visual and refractive outcomes in the short term.…”
Section: Surgical Problemsmentioning
confidence: 99%
“…The use of femtosecond laser in cataract surgery has become a common practice in cataract surgery to perform several steps of the surgical procedure: anterior capsulotomy, lens segmentation, and creation of corneal incisions [1]. It has been demonstrated that femtosecond lasers are able to generate clear corneal incisions (CCI) with minimal associated changes of anterior and posterior corneal topography, and comparable with those of single-plane angled manual incision [2] [3].…”
Section: Introductionmentioning
confidence: 99%